A Proper Shape of the Trailing Edge Modification to Solve a Housing Damage Problem in a Gas Turbine Power Plant - Thodsaphon Jansaengsuk; Mongkol Kaewbumrung; Wutthikrai Busayaporn; Jatuporn Thongsri (My University, 2021)
To solve the housing damage problem of a fractured compressor blade (CB) caused by an impact on the inner casing of a gas turbine in the seventh stage (from 15 stages), modifications of the trailing edge (TE) of the CB have been proposed, namely 6.5 mm curved cutting and a combination of 4 mm straight cutting with 6.5 mm curved cutting. The simulation results of the modifications in both aerodynamics variables Cl and Cd and the pressure ratio, including structural dynamics such as a normalized power spectrum, frequency, total deformation, equivalent stress, and the safety factor, found that 6.5 mm curved cutting could deliver the aerodynamics and structural dynamics similar to the original CB. This result also overcomes the previous work that proposed 5.0 mm straight cutting. This work also indicates that the operation of a CB gives uneven pressure and temperature, which get higher in the TE area. The slightly modified CB can present the difference in the properties of both the aerodynamics and the structural dynamics. Therefore, any modifications of the TE should be investigated for both properties simultaneously. Finally, the results from this work can be very useful information for the modification of the CB in the housing damage problem of the other rotating types of machinery in a gas turbine power plant.
Keywords: Trailing edge; Overall pressure ratio; Leading edge; Turbomachinery Performance and Optimization